(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Oscillating Water Column (OWC) devices are the most widespread among the different systems developed to harness the wave energy available on our coasts. Air turbines, normally used as Power Take Off (PTO) in these devices, are their most controversial part. Unidirectional turbines were first used with rectifying valves to take advantage of both characteristic operating stages of the OWC: exhalation and inhalation. The use of valves was quickly discarded and bidirectional turbines, which rotate in the same direction regardless whence the flow comes, were adopted as the most common solution despite reaching lower efficiencies than unidirectional ones. The Twin Turbine Configuration (TTC), based on the use of two unidirectional turbines, emerged then as a promising system, its main drawback being the duplicity of the equipment. The Double Decker Turbine (DDT) concept has been recently introduced to overcome these limitations since it combines in a single design the two typical solutions: self‐rectifying behaviour and the use of unidirectional turbines. In this work, the performance of a radial DDT, composed of an InFlow Radial (IFR) turbine and an OutFlow Radial (OFR) turbine, is assessed. A CFD model is used to design and optimize an IFR turbine to be mounted in combination with an OFR turbine taken from the literature. Finally, a non‐steady analysis is carried out assuming sinusoidal flow conditions. Results demonstrate that this radial version of the DDT could compete with its axial version and with other alternatives.